Etiology and Prognosis of Severe Ventriculomegaly Diagnosed at Late Gestation - Dall’Asta, Andrea; van Oostrum, Noortje H.M.; Basheer, Sheikh Nigel; Paramasivam, Gowrishankar; Ghi, Tullio; Galli, Letizia; Groenenberg, Irene AL; Tangi, Amanda; Accorsi, Patrizia; Echevarria, Monica; Angeles Rodríguez Perez, Maria; Albaiges Baiget, Gerard; Prefumo, Federico; Frusca, Tiziana; Go, Attie TJI; Lees, Christoph C. (Ultraschall in der Medizin - European Journal of Ultrasound, 2018)
Objectives We sought to assess the causes and outcomes of severe VM diagnosed de novo after 24 weeks of gestation where a mid-trimester anomaly scan was described as normal.Methods Multicenter retrospective study of five European fetal medicine centers. The inclusion criteria were normal anatomy at the mid-trimester scan, uni/bilateral finding of posterior ventricle measuring ≥ 15 mm after 24 weeks with neonatal and postnatal pediatric and/or neurological assessment data.Results Of 74 potentially eligible cases, 10 underwent termination, the outcome was missing in 19 cases and there was 1 neonatal death. Therefore, 44 formed the study cohort with a median gestation at diagnosis of 32 + 0 weeks (25 + 6 – 40 + 5). VM was unilateral in five cases. Agenesis of the corpus callosum (ACC) and grade III/IV intraventricular hemorrhage (IVH) accounted for 14 cases each. ACC was isolated in 9 fetuses. Obstructive abnormalities included 5 arachnoid and 1 cavum velum interpositum cyst. Four fetuses had an associated suspected or confirmed genetic condition, 2 congenital infections, 1 abnormal cortical development and the etiology was unknown in 3/44. Postnatal assessment at median 20 months (3 – 96) showed 22/44 (50 %) normal, 7 (16 %) mildly abnormal and 15 (34 %) severely abnormal neurodevelopmental outcomes.Conclusion One half of babies with severe VM diagnosed after 24 weeks have normal infant outcome with ACC and IVH representing the most common causes. Etiology is the most important factor affecting the prognosis of fetuses with severe VM diagnosed at late gestation.
Keywords: fetal neurosonography; central nervous system; antenatal ultrasound; third-trimester scan